2011
DOI: 10.1007/s10803-011-1383-x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion, Intent and Voluntary Movement in Children with Autism. An Example: The Goal Directed Locomotion

Abstract: This article focuses on the impact of intentionality on goal directed locomotion in healthy and autistic children. Closely linked with emotions and motivation, it is directly connected with movement planning. Is planning only preserved when the goal of the action appears motivating for healthy and autistic children? Is movement programming similar for autistic and healthy children, and does it vary according to the emotional valence of the object? Moving in a straight line, twenty autistic and healthy children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Moreover, motor problems are currently reported as associated features supporting the diagnosis of ASD (American Psychiatric Association [APA], 2013). To date, impairments have been highlighted in various motor domains including both gross and fine motor areas, motor coordination, postural control and standing balance (Fournier et al, 2010; Esposito et al, 2011; Longuet et al, 2012; Travers et al, 2013; May et al, 2016). The high variance in findings may suggest a broad spectrum of motor impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, motor problems are currently reported as associated features supporting the diagnosis of ASD (American Psychiatric Association [APA], 2013). To date, impairments have been highlighted in various motor domains including both gross and fine motor areas, motor coordination, postural control and standing balance (Fournier et al, 2010; Esposito et al, 2011; Longuet et al, 2012; Travers et al, 2013; May et al, 2016). The high variance in findings may suggest a broad spectrum of motor impairments.…”
Section: Introductionmentioning
confidence: 99%
“…4F ). This is reminiscent of the behavior of individuals with ASD, who take more time to initiate goal-directed actions and move more slowly during the initiation of those actions (Glazebrook et al, 2006; Longuet et al, 2012; Alvares et al, 2016). Further, individuals with ASD exhibit irregularities in audiovisual integration (Stevenson et al, 2014; Brandwein et al, 2015; Feldman et al, 2018), and the availability of multisensory information (auditory and visual) improves cricket hunting in wild type mice (Hoy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our FC analysis of a mouse model of ASD uncovered previously unknown impairment of cortical circuit function such as widespread hyperconnectivity, less modularized network during locomotion, and FC patterns involving M2 and M1 as the most distinctive signature for 15q dup mice. It has been reported that individuals with ASD exhibit motor coordination deficits and impairment of movement planning in goal-directed locomotion [10][11][12] . Although various factors could influence the locomotor activity of mice, reduced time spent for long locomotion in Emx1G615q dup mice might result from impaired motor planning and execution due to abnormal M2-related FC.…”
Section: Cortical Fc Abnormalities In 15q Dup Micementioning
confidence: 99%